2017
DOI: 10.26444/jpccr/75145
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin therapy and quality of life in diabetes

Abstract: Introduction. Diabetes is associated with a lower quality of life (QoL). Insulin therapy is perceived as an additional factor affecting QoL. The objective of this study, using standardized tools, was to evaluate to what extent insulin treatment has an effect on QoL in diabetes. Materials and method. 60 diabetic patients treated with insulin and 90 with oral drugs, all aged over 30, were included into the study. To assess the QoL of patients, SF-36 v.2 and WHOQOL-BREF questionnaires were used. In addition, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Many studies have examined the effect of insulin use on QOL in patients with diabetes; a 2019 study in Austria reported no statistical difference in the WHOQOL-BREF score between patients using insulin or patients treated with oral therapy [22] This result was like that of other studies which used the WHOQOL-BREF instrument [23,24] Nevertheless, other studies have concluded that insulin therapy improves QOL . In our study, insulin use was associated with lower psychological health.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Many studies have examined the effect of insulin use on QOL in patients with diabetes; a 2019 study in Austria reported no statistical difference in the WHOQOL-BREF score between patients using insulin or patients treated with oral therapy [22] This result was like that of other studies which used the WHOQOL-BREF instrument [23,24] Nevertheless, other studies have concluded that insulin therapy improves QOL . In our study, insulin use was associated with lower psychological health.…”
Section: Discussionsupporting
confidence: 53%
“…The copyright holder for this preprint this version posted June 23, 2021. ; https://doi.org/10.1101/2021.06.19.21259165 doi: medRxiv preprint of other studies which used the WHOQOL-BREF instrument [23,24] Nevertheless, other studies have concluded that insulin therapy improves QOL . In our study, insulin use was associated with lower psychological health.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effect of insulin use on QOL in patients with diabetes; a 2019 study in Austria reported no statistical difference in the WHOQOL-BREF score between patients using insulin or patients treated with oral therapy [22] This result was like that of other studies which used the WHOQOL-BREF instrument [23,24] Nevertheless, other studies have concluded that insulin therapy improves QOL [18,25] . In our study, insulin use was associated with lower psychological health.…”
Section: Discussionmentioning
confidence: 56%
“…[18][19][20] Because research on the link between different treatment regimens for type 1 diabetes (T1DM) and type 2 diabetes (T2DM) patients and QoL have not been consistent, it is essential to assess the correlations between these parameters. 21,22 In light of the foregoing, the current study's goal was to determine the prevalence of depression, cognitive impairment, and quality of life in T2DM patients. Furthermore, the impact of treatment type on depression, cognitive function, and QoL was studied.…”
Section: Resultsmentioning
confidence: 99%